Elevated Aminopeptidase P Attenuates Cerebral Arterial Responses to Bradykinin in Fawn-Hooded Hypertensive Rats - Khan, Md Abdul Hye (PLoS One, 2015)
Cerebral arterial myogenic and autoregulatory responses are impaired in Fawn Hooded hypertensive (FHH) rats. Cerebral autoregulatory responses are restored in the congenic rat strain in which a segment of chromosome 1 from the Brown Norway (BN) rat was transferred into the FHH genetic background (FHH.1BN). The impact of this region on cerebral arterial dilator responses remains unknown. Aminopeptidase is a gene that was transferred into the FHH genetic background to generate the FHH.1BN rats and is responsible for degradation of the vasodilator bradykinin. Thus, we hypothesized that FHH rats will have increased aminopeptidase P levels with impaired cerebral arterial responses to bradykinin compared to BN and FHH.1BN rats. We demonstrated higher cerebral arterial expression of aminopeptidase P in FHH compared to BN rats. Accordingly, we demonstrated markedly impaired cerebral arterial dilation to bradykinin in FHH compared to BN rats. Interestingly, aminopeptidase P expression was lower in FHH.1BN compared to FHH rats. Decreased aminopeptidase P levels in FHH.1BN rats were associated with increased cerebral arterial bradykinin-induced dilator responses. Aminopeptidase P inhibition by apstatin improved cerebral arterial bradykinin dilator responses in FHH rats to a level similar to FHH.1BN rats. Unlike bradykinin, cerebral arterial responses to acetylcholine were similar between FHH and FHH.1BN groups. These findings indicate decreased bradykinin bioavailability contributes to impaired cerebral arterial dilation in FHH rats. Overall, these data indicate an important role of aminopeptidase P in the impaired cerebral arterial function in FHH rat.